REGIONAL AUTONOMY AS A CONTROL SYSTEM IN PREVENTING CORRUPTION OF REGIONAL BUDGET - Zuhri Saifudin (Asia Pacific Fraud Journal, 2018)
The amendment to the 1945 Indonesian Constitution (UUD 1945) on local government has given authority to the local government to carry out its own regional autonomy. Article 18 paragraph (2), (4), and (6) of the constitution is the highest legitimacy related to regional autonomy. The dynamics of governance and regulations related to regional autonomy often change. The existence of Law No.23 of 2014 on Local Government is the last legal protection for the legitimacy of the local government to run its regional autonomy. Without any good regulations, the implementation of regional autonomy will be vulnerable to corruption. Robert Glitgaard defines corruption in a mathematical proposition with the following formula: (C = M + D-A) Corruption = Monopoly Power + Discretion by Official – Accountability. In carrying out the function of regional autonomy policy, the Regional Head has a big duty and authority. The duty of the Regional Head includes actively participating in issuing local legal products in the form of local regulations. The existence of this regulation can be used as a bastion for the Regional Head to manage the regional finances in the form of Regional Budget so as not to be corrupted. The type of research used in this study is normative perspective research. For the analysis, the author uses the formula of the principle of regional autonomy in the form of decentralization. The correlation of attribution, delegation, and mandate is used to examine the duties and authorities of the Regional Head in using the law. Based on the above background, the formulation of the problems includes: What is the correlation of the principle of regional autonomy for the Regional Head to avoid the abuse of authority and to prevent the occurrence of corrupt behavior? And, what is the ideal concept in the application of the Regional Regulation to prevent corruption of Regional Budget (APBD)? Correlation between regional autonomy policy and Regional Budget management cannot be separated from the existence of decentralization principle and policy pattern taken by the Regional Head. The parameters of Regional Budget change should be more detailed and studied deeply through Local Regulation as the highest legality, so that the potential for corruption will not occur.